Smoking Parameters in Coronary Heart Disease Patients Treated at Dr. Hasan Sadikin General Hospital Bandung, Indonesia (Majalah Kedokteran Bandung, 2024)
The association between smoking and coronary heart disease (CHD) has been studied extensively, though smoking parameters that contribute to the development of CHD may still need to be studied further. This cross-sectional study aimed to describe the characteristics of smoking parameters, including the number of cigarettes smoked, age when started smoking, duration of smoking, and cessation of smoking, in CHD patients treated at Dr. Hasan Sadikin General Hospital, Indonesia. CHD patients aged â‰¥18 years were included from the cardiology outpatient clinic and hospital wards. Smokers (current smokers/quit smoking
Keywords: Brinkman Index; coronary heart disease; coronary heart disease risk factor; smoking; smoking parameter